TECTONIC EVOLUTION OF THE BAIE VERTE MARGIN, NEWFOUNDLAND - Scorsolini, Ludovico (University of Waterloo, 2025)
Located along the Early Paleozoic Laurentian continental margin in Newfoundland, the Baie Verte Margin tectonistratigraphy and tectono-metamorphic evolution have been controversial for decades. Here, the results of a detailed field, petrological and geochronological study are presented, where Baie Verte Margin is subdivided into three tectono-metamorphic units separated by tectonic contacts: the East Pond Metamorphic Suite (EPMS) basement, EPMS cover, and the Fleur de Lys Supergroup (FdLS). Each unit exhibits a distinct metamorphic and structural evolution recorded during the subduction, exhumation, and post-collisional history of this ancient margin. The combination of thermodynamic modelling, petrochronology, and structural analysis provided insights into the P-T-t-d paths of the studied units, allowing a better understanding of their role during the evolution of the Taconic subduction system. High-pressure (HP) to ultra-high-pressure (UHP) conditions were reached between 483 and 475 Ma during the D1 phase, with the EPMS cover recording eclogite-facies metamorphism at ~2.8 GPa and 620°C. Subsequent decompression resulted in a β-shaped pressure-temperature-time (P-T-t) path, with near-isothermal decompression to ~2 GPa and heating to 860°C during exhumation. A multi-stage exhumation model is proposed for the EPMS eclogites: 1) buoyant rise through a low-density mantle wedge and 2) subsequent ascent at shallower crustal levels, facilitated by external tectonic forces and slab break-off, as evidenced by Late Taconic magmatism. While the EPMS cover re-equilibrated at UHP conditions, the EPMS basement and FdLS experienced decompression and Barrovian metamorphism during late-D1, indicating decoupling of the units during this stage. Coupling between the units occurred along a D2 shear zone during retrograde metamorphism, spanning 475–452 Ma. Two exhumation scenarios are proposed to explain the tectonic evolution of the margin: (i) Following late D1 detachment, the EPMS basement and FdLS were exhumed to crustal levels while the EPMS cover was subducted deeper into the mantle. Tectonic extrusion along D2 shear zones, potentially aided by melt weakening, then emplaced the EPMS cover between the two units. (ii) Alternatively, sequential detachment occurred from the top to the bottom of the slab, resulting in deeper subduction of lower units, followed by their exhumation through back-folding and crustal wedge thrusting. The Silurian F3 folding deforms both D1-2 structures in each unit and the D2 shear zones that bound them, suggesting that the continental wedges, which recorded different tectono-metamorphic paths after early D1, were juxtaposed before the onset of deformation associated with the Salinic Orogeny. Later deformation phases, D4 and D5, are probably related to tectono-metamorphic activity related to the Acadian and Neo-Acadian orogenies. This research improves our understanding of the dynamic tectono-metamorphic evolution of the Baie Verte Margin, emphasizing the role of fluids, thermal perturbations, and deformation in driving metamorphic reactions, and exhumation. The findings contribute to understanding the mechanisms controlling HP-UHP terrain evolution in subduction zones and highlight the complex interactions between subduction, exhumation, collision, and magmatism throughout the Taconic orogeny.
Keywords: Tectonics; NATURAL SCIENCES::Earth sciences::Endogenous earth sciences::Solid earth geology and petrology; Eclogites; Geochronology; Structural geology; Geochemistry